Pengaruh Ukuran Perusahaan, Leverage, Likuiditas, Profitabilitas, Dan Kepemilikan Manajerial Terhadap Kualitas Laba - Erdi Nandika; Sunarto Sunarto (Universitas Pendidikan Ganesha, 2022)
The purpose of this study was to analyze the effect of firm size, leverage, liquidity, profitability, and managerial ownership on qualityprofit. The sampling technique uses purposive sampling In this study, there were 39 companies with a total N of 117 but after the normality of the observation journal is 105. The analytical tool used is multiple linear regression analysis. The results of the analysis show that the size of company, leverage, liquidity and managerial ownership have no effecton earnings quality; while profitability has a positive effect on quality profit. Keywords : Firm Size, Leverage, Liquidity, Profitability, Managerial Ownership, Earnings Quality